Novalis and the problem of the original action of the I - Silva, Fernando (Revista de Filosofía, 2019)
Between 1795 and 1796 Novalis produces a vast group of fragments on Fichte’s philosophy, the posthumously entitled “Fichte-Studien”. Among the topics therein approached, one of the most important is that of the original action of the I (Urhandlung), and the possible or impossible union of the opposites which model human life and thought, feeling and reflection. The aim of this article is to inquire Novalis’ view of this problem of paramount importance for a philosophy of the I; namely, to investigate the contours of Novalis’ circular conception of the problem, and its differences regarding Fichte; to expound the dilemma of the necessity and yet impossibility of a union between opposites; and to show how the young philosopher considers this problem both in its real and in its ideal prism, thereby proposing, as a solution, a union in disunion, an (im-)possible union between opposites, which Novalis affirms as a new conception of the circular study of the I and as the foundation for a new philosophizing.